2015
DOI: 10.1021/acs.analchem.5b02594
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Immunoassay with a Surface Acoustic Wave Device and a Highly Stable Protein Monolayer for On-Site Monitoring of Airborne Dust Mite Allergens

Abstract: This work describes a sensor to be incorporated into the on-site monitoring system of airborne house dust mite (HDM) allergens. A surface acoustic wave (SAW) device was combined with self-assembled monolayers of a highly stable antibody capture protein on the SAW surface that have high resistance to pH change. A sandwich assay was used to measure a HDM allergen, Der f 1 derived from Dermatophagoides farinae. Capture antibodies were cross-linked to a protein G based capture layer (ORLA85) on the sensor surface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…1(b)]. (18)(19)(20) The surface modification of the sensing area with the SAM was carried out as per the manufacturer's protocol: the surface was initially rendered hydrophilic in order to prevent nonspecific hydrophobic adsorption of ORLA85 by incubating the sensing area with 1% (v/v) BME in ultrapure water for 5 min. (21) Afterwards, in order to form the Au-S bond between ORLA85 and the gold on the SAW device, disulfide bonds of ORLA85 were reduced by mixing the protein solution with TCEP solution (TCEP 7.5 mg/mL in Tris-HCl) and letting stand for 30 min.…”
Section: Fabrication Of Saw Immunosensormentioning
confidence: 99%
See 2 more Smart Citations
“…1(b)]. (18)(19)(20) The surface modification of the sensing area with the SAM was carried out as per the manufacturer's protocol: the surface was initially rendered hydrophilic in order to prevent nonspecific hydrophobic adsorption of ORLA85 by incubating the sensing area with 1% (v/v) BME in ultrapure water for 5 min. (21) Afterwards, in order to form the Au-S bond between ORLA85 and the gold on the SAW device, disulfide bonds of ORLA85 were reduced by mixing the protein solution with TCEP solution (TCEP 7.5 mg/mL in Tris-HCl) and letting stand for 30 min.…”
Section: Fabrication Of Saw Immunosensormentioning
confidence: 99%
“…It suggested that parallel measurement of different HDM allergens, Der f 1 and Der f 2, would be possible by combining it with the previously developed Der f 1 SAW immunosensor, because the Der f 1 sensor also showed high selectivity to Der f 1. (18) …”
Section: Characterization Of Der F 2 Saw Immunosensormentioning
confidence: 99%
See 1 more Smart Citation
“…Deoxyribonucleic acid (DNA) detection was demonstrated by Sakong et al [ 39 ] using complementary binding between a probe and a target on a gold-coated SH-SAW device fabricated on a LiTaO 3 substrate. More recently, SH-SAW devices have been used to monitor airborne allergens in a semi-continuous manner over a period of 4 days with a detection limit of 6.1 ng/ml established for a house dust mite allergen Der f 1 [ 40 ].…”
Section: Surface Acoustic Wave Resonatorsmentioning
confidence: 99%
“…SAW devices are the major components of electronic devices used in various fields as filters, frequency duplexers, and radio frequency identification (RFID) tags [5][6][7][8][9]. In addition, SAW devices are widely used in biochemical detection, drug development, life sciences, and medical research.…”
Section: Introductionmentioning
confidence: 99%